2021
DOI: 10.3389/feart.2021.633698
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Climate Controls in Triple Oxygen (16 O, 17 O, 18 O) and Hydrogen (1 H, 2 H) Isotopes Composition of Rainfall (Central Pyrenees)

Abstract: Studies of rainfall isotopic composition in the Iberian Peninsula are scarce, and to date, none of them have provided analyses of the triple oxygen isotopes, preventing from the complete understanding of current atmospheric processes in this region. We investigate the rainwater δ17O, δ18O, and δD and derived parameters 17O-excess and d-excess in a mountain site in the Central South Pyrenees (Villanúa, Huesca, Spain) to identify the main factors (regional and local) controlling the isotopic composition of preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…This evaporation was inferred from seasonal δ ′ 18 O– δ ′ 17 O and δ 18 O– δ 2 H regression lines (Figure S5 in Supporting Information ). A strong positive correlation ( r = 0.75) and positive slope (1.1 per meg ‰ −1 ) between summer ∆′ 17 O and d ‐excess and a slight positive correlation between summer ∆′ 17 O values and local relative humidity ( r = 0.19) support this interpretation (Gimenez et al., 2021; Landais et al., 2010). These signals are most likely related to sub‐cloud evaporation during small summer storms (e.g., Benjamin et al., 2004; Eastoe & Dettman, 2016; Friedman et al., 2002; Marchetti & Marchetti, 2019).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This evaporation was inferred from seasonal δ ′ 18 O– δ ′ 17 O and δ 18 O– δ 2 H regression lines (Figure S5 in Supporting Information ). A strong positive correlation ( r = 0.75) and positive slope (1.1 per meg ‰ −1 ) between summer ∆′ 17 O and d ‐excess and a slight positive correlation between summer ∆′ 17 O values and local relative humidity ( r = 0.19) support this interpretation (Gimenez et al., 2021; Landais et al., 2010). These signals are most likely related to sub‐cloud evaporation during small summer storms (e.g., Benjamin et al., 2004; Eastoe & Dettman, 2016; Friedman et al., 2002; Marchetti & Marchetti, 2019).…”
Section: Discussionmentioning
confidence: 86%
“…First, nearly every precipitation δ ′ 18 O– δ ′ 17 O slope is less than 0.528. Second, on seasonal timescales, nearly every previous study of precipitation and water vapor has reported higher δ ′ 18 O– δ ′ 17 O regression slopes in the winter and lower δ ′ 18 O– δ ′ 17 O regression slopes in the summer (Affolter et al., 2015; Gimenez et al., 2021; He et al., 2021; Surma et al., 2021; Tian et al., 2018; Tian & Wang, 2019; Uechi & Uemura, 2019). This seasonal pattern leads to higher ∆′ 17 O values in the winter and lower ∆′ 17 O values in the summer (Figure 4a).…”
Section: Discussionmentioning
confidence: 96%
“…The high-altitude setting of Serra da Estrela results in temperature being an important driver of moisture condensation and the δD value of precipitation (δD prc ) (Carreira et al, 2009;Oliveira and Lima, 2010). This is reflected by a strong relationship between mean values of δ 18 O and δD vs. temperature of monthly rainfall for Portugal's mainland (Carreira et al, 2009), which is also observed in other Iberian mountains (Giménez et al, 2021). The combination of the settings mentioned above and climatic and environmental factors makes Serra da Estrela one of the most biodiverse in Europe (Jansen, 2011) and a prime location to investigate the relationship between climate and ecology (Connor et al, 2021).…”
Section: Study Areamentioning
confidence: 93%
“…(2021) for Singapore, Table S2 in Uechi and Uemura (2019) for Okinawa Island, https://doi.org/10.1594/PANGAEA.895300 and Tian and Wang (2019) for Indianapolis in the U.S., Supplementary Table 3 in Giménez et al. (2021) for the Pyrenees in Spain, Figures 4 and 6 in Affolter et al. (2015) for Mormont in Switzerland, and Figures 7–13 in Leuenberger and Ranjan (2021) for other Switzerland sites.…”
Section: Data Availability Statementmentioning
confidence: 99%